Minimally invasive therapy for fetal sacrococcygeal teratoma: case series and systematic review of the literature. (8th May 2014) - Van Mieghem, T.; Al‐Ibrahim, A.; Deprest, J.; Lewi, L.; Langer, J. C.; Baud, D.; O'Brien, K.; Beecroft, R.; Chaturvedi, R.; Jaeggi, E.; Fish, J.; Ryan, G.
<x xml:space="preserve">Abstract</x> Linked Comment: Ultrasound Obstet Gynecol 2014; 43: 609–609